Histone tails as signaling antennas of chromatin. (April 2021) - Peng, Yunhui; Li, Shuxiang; Landsman, David; Panchenko, Anna R
Highlights: Intrinsic disorder empowers histone tails' diverse roles in chromatin signaling. Introducing PTMs and histone variants dramatically enhances the functional diversity of histone tails. Interactions of histone tails with nucleosomal and linker DNA modulate the nucleosome recognition by binding partners. Histone tail cleavage regulates chromatin structure and function. Histone tails play critical roles in the formation of higher-order chromatin structure. Abstract : Histone tails, representing the N-terminal or C-terminal regions flanking the histone core, play essential roles in chromatin signaling networks. Intrinsic disorder of histone tails and their propensity for post-translational modifications allow them to serve as hubs in coordination of epigenetic processes within the nucleosomal context. Deposition of histone variants with distinct histone tail properties further enriches histone tails' repertoire in epigenetic signaling. Given the advances in experimental techniques and in silico modelling, we review the most recent data on histone tails' effects on nucleosome stability and dynamics, their function in regulating chromatin accessibility and folding. Finally, we discuss different molecular mechanisms to understand how histone tails are involved in nucleosome recognition by binding partners and formation of higher-order chromatin structures.